12.75x-15.35=3.124(2x+3)

Simple and best practice solution for 12.75x-15.35=3.124(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12.75x-15.35=3.124(2x+3) equation:


Simplifying
12.75x + -15.35 = 3.124(2x + 3)

Reorder the terms:
-15.35 + 12.75x = 3.124(2x + 3)

Reorder the terms:
-15.35 + 12.75x = 3.124(3 + 2x)
-15.35 + 12.75x = (3 * 3.124 + 2x * 3.124)
-15.35 + 12.75x = (9.372 + 6.248x)

Solving
-15.35 + 12.75x = 9.372 + 6.248x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6.248x' to each side of the equation.
-15.35 + 12.75x + -6.248x = 9.372 + 6.248x + -6.248x

Combine like terms: 12.75x + -6.248x = 6.502x
-15.35 + 6.502x = 9.372 + 6.248x + -6.248x

Combine like terms: 6.248x + -6.248x = 0.000
-15.35 + 6.502x = 9.372 + 0.000
-15.35 + 6.502x = 9.372

Add '15.35' to each side of the equation.
-15.35 + 15.35 + 6.502x = 9.372 + 15.35

Combine like terms: -15.35 + 15.35 = 0.00
0.00 + 6.502x = 9.372 + 15.35
6.502x = 9.372 + 15.35

Combine like terms: 9.372 + 15.35 = 24.722
6.502x = 24.722

Divide each side by '6.502'.
x = 3.802214703

Simplifying
x = 3.802214703

See similar equations:

| 2(5a-1)-4(-2a+3)= | | 21+9j+-10=-277 | | 1-6x=7+3x-8x | | y-(-75)=60 | | 13x-15=3(2x+3) | | 2x^3-12x^2-3x+192=0 | | 12x-15=3(2x+4) | | 8c=54 | | 7n+2n=81 | | 27x-1=19x+14+5x | | 4c-5+14c= | | 13=4x+-11 | | x/3=-19 | | 2(x+8)-4=2(x-7)+8 | | x-5[2x-3(x+6)]=-4(x-5) | | -11.3x=101.7 | | 3y+6=y^2 | | =6t | | 2.5-4f=10-2.5f | | (X+10)=(2x+5) | | =10y-15y | | -10=(a-1)+(a-3) | | 28=m-4 | | x^3-16y=0 | | -4(2b+1)+(9b-7)=0 | | 7j-25=2j | | 3x+1-3x-3x-1=45 | | 6+2m=-3+5m | | x^4-6x^3+10x^2-9=0 | | x^2+(3x^2-30x+25)=25 | | 2xj+3=17 | | 4x^2+15x=175 |

Equations solver categories